Urtica dioica, a weed with many possibilities - Ankarcrona, Johanna (2019)
The aim of this study was to investigate the nutritional value of Urtica dioica and suggest the application of U. dioica as part of a healthy diet. U. dioica, or commonly known as stinging nettle, is a perennial plant growing almost all over the world. It prefers moist soils with a high nitrogen content. When the plant comes in contact with the skin it releases small tubes which contain irritative substances which penetrates the skin giving a rash and a burning feeling. For cultivation it can be grown with low input and can give a relatively good yield for many years. It has been used for centuries as a food source and in folk medicine. In Sweden U. dioica is traditionally picked in spring and used to make “nettle soup”. U. dioica can be purchased dried as powder, in capsules or as tea for example. According to the EAT Lancet report, the consumption of meat products should be decreased whereas fruits and vegetables should be consumed in higher portions. With its highly nutritious content, U. dioica can be included in such a diet. It contains vitamins, minerals, essential fatty acids and has a relatively high protein content. Nine carotenoids have been detected in U. dioica. Pigment from U. dioica can be extracted and used for food coloring (E140). Nitrate has a tendency to accumulate in the plant and therefore it should not be picked on soils which have high nitrogen levels. Water extraction from U. dioica is a good source of antioxidants which are health promoting in different ways. The anti-oxidant properties of U. dioica are probably due to presence of phenolic compounds. U. dioica have antibacterial properties against certain bacteria such as Staphylococcus aureus. S. aureus bacterium have strains that are antibiotic resistant which particularly causes problems in hospitals. Therefore, it is important to develop alternatives to the traditional antibiotics. U. dioica even contains substances with anticarcinogenic properties. As used externally, it can be applied fresh to relieve joint pain. U. dioica as a part of the diet has therefore many advantages but more studies need to be done to confirm its properties and elucidate the mechanism responsible for them.